Calibration of the dynamic behaviour of incomplete structures in archeological sites: the case of Villa Diomede portico in Pompeii. (2017) - Lorenzoni, F.; Valluzzi, M.R.; Minello, A.; Salvalaggio, M.; Modena, C.
Abstract: This paper reports the research activities carried out on Villa Diomede in Pompeii, built during the "Pre-Roman period" (i.e. the 3rd century BC) and discovered between 1771 and 1774 during the archaeological excavations. It is one of the greatest private buildings of Pompeii and it is located on the western corner of the modern archeological site. Three levels compose the building: the ground floor, the lower quadriportico with a square plan and a series of colonnades on the four sides around the inner garden and the cryptoportico. Villa Diomede was damaged by the strong earthquake occurred in AD 63 that caused the collapse of the western pillars of the quadriportico and later damaged after the big eruption of Vesuvius in AD 79. In June 2015 a series of nondestructive tests (NDT) were carried out by the authors in order to obtain information on the state of conservation of the building and to assess its structural behavior. Direct and tomographic sonic pulse velocity tests, ground penetrating radar, endoscopies and operational modal analysis were performed on the remaining structural elements on the two levels of the Villa. The present paper reports the main outcomes and findings of ambient vibration tests implemented to extract the modal parameters in terms of eigenfrequencies, mode shapes and damping ratios. Operational modal analysis and output-only identification techniques were applied to single stone pillars of the quadriportico structure and then to the entire square colonnade of Villa Diomede. Results are then used to study the soil-structure interaction at a local level and extend the gained information for the numerical calibration of the whole structure. Thanks to this methodology a detailed model updating procedure of the quadriportico was performed to develop reliable numerical models for the implementation of advance structural and seismic analysis of this "incomplete" archaeological structure.